Pengaruh Rekrutmen Dan Motivasi Karyawan Terhadap Kinerja Karyawan PT Alfamart Cileungsi - Neng Elisnawati; Suhardoyo Suhardoyo; Lela Elvira (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study aims to determine the Effect of Recruitment, Employee Motivation on Employee Performance at PT Alfamart Cileungsi. The research method used is a quantitative research method with primary data obtained from questionnaire data measured using a Likert scale. The population of this research is employees of PT Alfamart, especially in the recruitment, learning and development section. The sampling technique used in this study was to use a saturated sample with a total of 45 respondents. The data analysis technique used was multiple linear regression which was processed with the help of the IBM SPSS 26 for Windows program. The results of this study prove that the influence of recruitment has an effect on employee performance, employee motivation has an effect on employee performance at PT Alfamart Cileungsi.